2001
DOI: 10.1359/jbmr.2001.16.7.1212
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between Changes in Bone Mineral Density Measured at Different Skeletal Sites in Perimenopausal Women—Implications for Assessment of Bone Loss and Response to Therapy: The Danish Osteoporosis Prevention Study

Abstract: Assessing bone loss and gain is important in clinical decision-making, both in evaluating treatment and in following untreated patients. The aim of this study was to correlate changes in bone mineral density (BMD) at different skeletal sites during the first 5 years after menopause and determine if forearm measurements can substitute for dual-energy X-ray absorptiometry (DXA) of the spine and hip. BMD was measured at 0, 1, 2, 3, and 5 years using Hologic 1000/W and 2000 densitometers in 2016 perimenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Most of these discordances (38.9%) are from minor category, presenting difference on only one class, and could be due to minor variation in BMD techniques or some minor physiologic dissimilarity. Minor discordance generally does not influence the overall prognosis of patients; however, in the case of patients with one site normal and the other osteopenic, follow up of patients with hip osteopenia seems reasonable [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of these discordances (38.9%) are from minor category, presenting difference on only one class, and could be due to minor variation in BMD techniques or some minor physiologic dissimilarity. Minor discordance generally does not influence the overall prognosis of patients; however, in the case of patients with one site normal and the other osteopenic, follow up of patients with hip osteopenia seems reasonable [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that T-score discordance can affect diagnosis and management of postmenopausal osteoporosis [9][10][11][12][13][14]. Inconsistencies in the diagnostic classification between skeletal sites also can be present in premenopausal women.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Even within an individual subject, there is discordance of T scores between different sites, and this is especially pronounced in postmenopausal women. 7 Thus, whether a person is classified as having osteoporosis or not based on BMD measurement may depend on the site of measurement. Therefore, there is a drive to standardize the site used for diagnosis, and total hip has been proposed as the standard since it has the highest predictive value of all current techniques assessed prospectively, and it is less affected than the spine by osteoarthrosis and osteoarthritis with age.…”
Section: Bmd and Fracture Riskmentioning
confidence: 99%